Retinal vascular resistance in arterial hypertension - Dennis Kannenkeril; Joanna M. Harazny; Agnes Bosch; Christian Ott; Georg Michelson; Roland E. Schmieder; Stefanie Friedrich (Blood Pressure, 2018)
Purpose: Retinal microcirculation represents an easily accessible, non-invasive, in-vivo possibility to assess early microvascular changes. In addition to the assessment of functional (e.g. retinal capillary flow, RCF) and retinal arteriolar structural parameters (e.g. wall-to-lumen-ratio, WLR) we now suggest a new parameter reflecting the resistance in small retinal arterioles (RVR). Material and methods: In 45 normotensive (NT) subjects and 123 patients with hypertension stage 1 (HT) we assessed RCF, WLR, arteriolar diameter, lumen diameter and wall cross section area in the retinal circulation by using scanning laser Doppler flowmetry (SLDF). Mean arterial pressure (MAP) was measured immediately before the SLDF measurement and retinal vascular resistance was calculated (RVR = MAP/RCF). In a separate study the test-retest reliability was determined in 6 volunteers from our clinical staff by assessing RVR three times within six weeks. Results: The analysis of the volunteers revealed a coefficient of variation for RVR of 7.75 ± 2.11% and Cronbach´s alpha was 0.90. WLR, a marker of vascular remodeling did not differ between NT and HT. In contrast, RCF and inner diameter of the retinal arterioles (ID) were significantly lower (RCF: p = .045 and ID: p = .001) in the HT group than in the NT group and RVR was significantly higher in the HT group than in the NT group (p < .001). In both groups we found no correlation of RVR with age, but a significant correlation of RVR with WLR (NT: r = 0.34, p = .006; HT: r = 0.25, p = .01), indicating that the RVR reflects vascular remodeling in the retinal circulation. Conclusion: Our data showed an increased retinal vascular resistance in hypertensive patients compared to non-hypertensive patients prior to the occurrence of structural retinal vascular remodeling. The correlation between RVR and WLR indicates that RVR is a reliable, non-invasive and early-sensitive marker of vascular remodeling in early hypertension.